Importância da segregação de materiais no gerenciamento de lixo hospitalar na área de hemoterapia - Cotrim, Ondina Silvia; Slob, Edna; Deffune, Elenice [UNESP] (My University, 2012)
In recent years the environment and its effects on human life has been the subject of research. The scientific society organized to manage the problem of large amount of waste generated, discuss the degradation of the environment and point out possible solutions. The scarcity of references in the specific hemotherapy motivated this research. This study is an observational descriptive in order to raise the issue of hospital waste specific area of hemotherapy, presenting its latest ratings on Brazilian law also highlights the proposed Waste Management Program Health Service (PGRSS) Blood Center of Botucatu (HB) highlighting the importance of segregation of noble material in the generation of other therapeutic products using the technique of cleaner production (CP). The observational analysis of the reports shows a 20-fold increase in the amount of waste generated from 1993 to 2005, while the increase of manpower was 2.5 times. The increase in generation was due RSS hemocenter deployment of automated techniques, increased demand and improved sorting of waste. The technique implanted P + L in 2001 began using units of fresh frozen plasma, previously discarded after 12 months of storage, for the composition of new therapeutics for topical use, called bio dressing. In 10 years of implementation of this new technique, therapeutic products generated 535 patients benefited from micro-Botucatu.

Nos últimos anos o meio ambiente e seus reflexos na vida do homem tem sido motivo de pesquisas. A sociedade científica organiza-se para gerenciar o problema da grande quantidade de resíduos gerados, discutir a degradação do meio ambiente e apontar as suas possíveis soluções. A escassez de referências na área específica da hemoterapia motivou esta pesquisa. Este trabalho é um estudo observacional do tipo descritivo com a finalidade de levantar a questão do resíduo hospitalar específico da área de hemoterapia, apresentando suas recentes classificações diante da legislação brasileira além de evidenciar proposta do Programa de Gerenciamento de Resíduos de Serviço de Saúde (PGRSS) do Hemocentro de Botucatu (HB) destacando a importância da segregação de material nobre na geração de outros produtos terapêuticos utilizando a técnica de produção mais limpa (P+L). A análise observacional dos relatórios mostra um aumento de 20 vezes na quantidade de resíduo gerado de 1993 a 2005, enquanto que o aumento de recursos humanos foi de 2,5 vezes. O aumento na geração de RSS do hemocentro se deveu a implantação de técnicas automatizadas, aumento da demanda e melhora na classificação dos resíduos. A técnica P+L implantada em 2001 passou a utilizar unidades de plasma fresco congelado, anteriormente descartado após 12 meses de armazenamento, para a composição de novas formas terapêuticas de uso tópico, denominadas de biocurativo. Em 10 anos de implantação desta nova técnica, os produtos terapêuticos gerados beneficiaram 535 pacientes da microrregião de Botucatu.
Importance of segregation of materials in hospital waste management area hemotherapy
Keywords: Waste management waste health service hospital; Environmental management; Bio dressing; Gerenciamento de resíduos de serviço de saúde; Resíduo hospitalar; Gestão ambiental; Biocurativo